2014
DOI: 10.1186/1471-2407-14-566
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and prognostic significance of preoperative plasma hyperfibrinogenemia in gallbladder cancer patients following surgical resection: a retrospective and in vitro study

Abstract: BackgroundCoagulation and fibrinolysis activation is frequently observed in cancer patients, and the tumors in these cases are thought to be associated with a higher risk of invasion, metastasis, and worse long-term outcome. The objective of this study was to elucidate the prognostic significance of blood coagulation tests and various clinicopathological characteristics in patients with gallbladder cancer (GBC) after surgical resection.MethodsWe retrospectively reviewed the medical records of 115 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
92
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 29 publications
(31 reference statements)
5
92
2
Order By: Relevance
“…7,25,26 Fibrinogen can regulate cellular adhesion, proliferation, and migration through interactions with fibroblast growth factor 2 (FGF-2) and vascular endothelial growth factor (VEGF). 27 By increasing the expression of vimentin and reducing the expression of E-cadherin, Shu et al 17 demonstrated that highly concentrated fibrinogen induced epithelial-mesenchymal transition (EMT), which confers migration, invasion, and metastatic capacity and multidrug resistance to tumor cells. 28,29 Fibrinogen may act as ligands for integrin and non-integrin receptors, which were found on tumor cells, stromal cells, and inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,25,26 Fibrinogen can regulate cellular adhesion, proliferation, and migration through interactions with fibroblast growth factor 2 (FGF-2) and vascular endothelial growth factor (VEGF). 27 By increasing the expression of vimentin and reducing the expression of E-cadherin, Shu et al 17 demonstrated that highly concentrated fibrinogen induced epithelial-mesenchymal transition (EMT), which confers migration, invasion, and metastatic capacity and multidrug resistance to tumor cells. 28,29 Fibrinogen may act as ligands for integrin and non-integrin receptors, which were found on tumor cells, stromal cells, and inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Fibrinogen has recently been shown to play vital roles in tumorigenesis and contributed to angiogenesis, stroma formation, and hematogenous metastasis of tumor cells. [7][8][9][10] Elevated plasma fibrinogen level is related with tumor progression and other poor outcomes in several types of malignancies, for example, covered esophageal cancer, 11 gastric cancer, 12 pancreatic cancer, 13 colon cancer, 14 lung cancer, 15 hepatocellular cancer, 16 gallbladder cancer, 17 and gynecological cancer. [18][19][20][21] For operable breast cancer patients, elevated preoperative plasma fibrinogen level is demonstrated to be associated with cancer progression and is independently associated with a poor prognosis in patients.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, fibrinogen, a 340 kD liver glycoprotein, has been shown to play an essential role in both systemic inflammatory responses and tumor progression 10,11. Many investigators have demonstrated the clinical utility of fibrinogen as a prognostic predictor in various types of malignancies 12,13. Recently, a new scoring system combining preoperative fibrinogen and the NLR (F-NLR) has been demonstrated as a promising prognostic marker for esophageal squamous cell carcinoma 14,15.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, links between hyperfibrinogenemia and malignancies such as breast, gastric, lung, colorectal, pancreatic, and endometrial cancers have been increasingly recognized [14][15][16][17][24][25][26]. A previous retrospective study demonstrated that the preoperative plasma fibrinogen level was an independent marker of poor prognosis in gallbladder cancer patients following surgical resection [19]; however, no data have been reported on the clinicopathological and prognostic value of baseline plasma fibrinogen concentrations in patients with BTC. To the best of our knowledge, this is the first report that the plasma fibrinogen concentration at the time of diagnosis is an independent prognostic factor in patients with ABTC.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, our unpublished data indicate that changes in plasma fibrinogen concentration before and after surgery are significantly correlated with survival in gastric cancer patients undergoing D2 curative surgery. A newly published study reported that the preoperative plasma fibrinogen level was associated with tumor progression in gallbladder cancer patients following surgical resection [19]. However, the relationship between plasma fibrinogen concentration and clinical outcomes in patients with resectable and unresectable BTC is still unknown.…”
Section: Introductionmentioning
confidence: 96%